European Policies towards Palm Oil - Sorting Out some Facts - Gernot Pehnelt; Christoph Vietze (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2009)
This paper analyses the role of palm oil and its sustainability from different perspectives. We consider the role of palm oil within the GHG context. We discuss the impact of palm oil on biodiversity and analyse how palm oil can contribute to economic growth and development in tropical countries. Finally, based on this analysis, we assess the current concerns about and politics towards palm oil with special focus on the EU. Palm oil is a low-energy and low-fertilizer crop that offers much higher yields per hectare than other oil crops. Furthermore, if the energy obtained by the residuals in the production process is used properly, the energy balance of palm oil production is much more favourable compared to other biofuels. Overall, palm oil turns out to be much more efficient than other oil crops and therefore offers significant advantages within the context of GHG savings. Contrary to some recent campaigns and the perception among European citizens, oil palm plantings are not a major contributor to deforestation in tropical countries. Deforestation associated with oil palm plantings is much less significant than postulated by some recent campaigns. Furthermore, biodiversity in oil palm plantations is much higher than in most monocultures in the EU. Palm oil is an important driver of economic development and growth in tropical countries and contributes to the reduction of poverty and hunger in the developing world. The EU Renewable Energy Directive is discriminatory from the outset and the GHG saving values and their interpretation are based on wrong assumptions and faulty calculations. Therefore, the EU should reshape its policies towards palm oil, conduct objective and non-discriminatory calculations regarding the GHG emissions saving values and support palm oil imports from developing countries rather than restricting them. Together with certain initiatives to further enhance energy efficiency and to protect precious habitats combined with strategies to strengthen property rights and encourage efficient land use and successful strategies of agricultural development, this would not only prevent political conflicts and trade disputes in conjunction with the issue of palm oil but also foster economic growth and development, reduce poverty and - not least - contribute to the ambitious GHG emissions savings goals on a fair and reasonable basis
Keywords: F14; F18; O13; Q01; Q15; Q27; Q56; Q57; 330; Renewable Energy; Palm Oil; Biodiversity; Sustainable Development; Environmental Policy; Palmöl; Pflanzenbau; Bewertung; Bioenergie; Klimaschutz; Biodiversität; EU-Umweltpolitik; Entwicklungshilfe; EU-Europäisch; Nachhaltige Entwicklung; EU-Staaten; Tropen; Entwicklungsländer